ESTIMATION OF NUTRITIONAL LEVEL OF RURAL POPULATION LIVING ON RADIOACTIVELY CONTAMINATED TERRITORIES IN THE CONTEXT OF FOOD SAFETY GUARANTEE - O. Skydan; L. Romanchuk; V. Dovzhenko (Наукові горизонти, 2019)
It has been determined that the problem of food safety is the issue of the day for Ukraine, and its solution is the area of ensuring national security and implementing effective agrarian policy. The emphasis is placed on the need to take into account the radioactive contamination factor in the process of development of the appropriate measures to guarantee food security. It has been proved that there are certain problems in providing the rural population of radioactively contaminated territories with high quality and healthy food products. The emphasis is on the significant amount of home-grown products which form part of the diet of the rural population on the territory of radioactive contamination and may pose a threat to human health. Quantitative parameters of consuming products produced on the contaminated territory has been studied. In particular, it has been determined that most villagers consume milk and potatoes of their own production, and the consumption of berries and fruit grown on subsidiary farm plots is significant. However, the biggest concern is that more than half of the rural population consume forest berries, the level of radioactive contamination of which exceeds the permissible standards. It has been found that the vital interests of rural residents of contaminated areas are not protected; that is, there is no guarantee that, even if the necessary food products are available, they are safe and high-quality ones. Therefore, the state should pay more attention to the establishment of the system for monitoring the level of radiological contamination of food products in order to reduce individual radiation doses of the population living in rural areas on the territory of radioactive contamination.